2022
DOI: 10.3390/ijms231710099
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol versus Other Selected Drugs in the Treatment of Various Types of Anxiety or Stress, with Particular Reference to Stage Fright and Post-Traumatic Stress Disorder

Abstract: Propranolol, a non-cardioselective β1,2 blocker, is most commonly recognised for its application in the therapy of various cardiovascular conditions, such as hypertension, coronary artery disease, and tachyarrhythmias. However, due to its ability to cross the blood–brain barrier and affinity towards multiple macromolecules, not only adrenoreceptors, it has also found application in other fields. For example, it is one of the very few medications successfully applied in the treatment of stage fright. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 186 publications
1
7
0
1
Order By: Relevance
“…However, comparing our findings with previous studies conducted in Saudi Arabia, it was found that self-medication was prevalent among 60.5% of the participants and that 63.2% of them had taken propranolol at a dose of < 10 mg [ 13 , 21 , 24 , 26 ]. The highest reported dose was 40 mg, which was close to the highest reported dose in our results [ 28 ]. Only 15.8% (n=6) of participants at Umm Al-Qura University increased their dosage without a physician’s instructions; according to Alkhatabi et al, 29.4% of their participants increased their dosage without a physician’s instructions [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, comparing our findings with previous studies conducted in Saudi Arabia, it was found that self-medication was prevalent among 60.5% of the participants and that 63.2% of them had taken propranolol at a dose of < 10 mg [ 13 , 21 , 24 , 26 ]. The highest reported dose was 40 mg, which was close to the highest reported dose in our results [ 28 ]. Only 15.8% (n=6) of participants at Umm Al-Qura University increased their dosage without a physician’s instructions; according to Alkhatabi et al, 29.4% of their participants increased their dosage without a physician’s instructions [ 26 ].…”
Section: Discussionsupporting
confidence: 86%
“…In spite of the abovementioned, the systematic review and meta-analysis conducted by Steenen et al concluded, that currently there is no sufficient evidence for the routine administration of propranolol in case of any anxiety disorders ( Steenen et al, 2016 ). Moreover, another meta-analysis also showed a lack of evidence of satisfactory quality to determine, whether or not to use propranolol in the treatment of stage fright ( Szeleszczuk and Frączkowski, 2022 ).…”
Section: Propranolol–an Old Drug With New Propertiesmentioning
confidence: 99%
“…However, its use may be dependent on the type of disorder, showing promise for posttraumatic stress disorder but limited controversial evidence for long-term management of anxiety. 78,79…”
Section: Psychiatric Medicationsmentioning
confidence: 99%